TRANSFORMATION OF TRADITIONAL DAYAK ARCHITECTURE ELEMENTS IN GOVERNMENT BUILDING DESIGNS IN KUTAI KERTANEGARA (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Abstract Traditional Dayak architecture is often used as a source of ideas or design inspiration for the functions of government buildings or other public buildings in Kalimantan. The application of traditional architectural elements using repetition is a common phenomenon in almost all regions of Kalimantan, including in Kutai Kertanegara Regency, East Kalimantan Province. Regarding this, this study aims to assess the transformation of the traditional values ​​of the Dayak people and their traditional architectural forms in the design of government buildings in the Kutai Kertanegara Regency. The selection of government buildings as the object of study is based on their form and appearance that are easily recognized and familiar to the public. The study method was chosen using a comparison technique between the functions, roles, and values ​​of traditional Dayak architectural elements with their existence in buildings with new functions. The results obtained from this study are the discovery of several traits and characters of Dayak traditional elements in public buildings in the form of shapes, colors, motifs, and ornaments. The use of flimsy shields on the facades and interiors is quite prominent as an option in its implementation on the facades of government buildings. The colors that are widely explored and applied to walls and facades are colors that symbolize greatness (yellow), eternity, repellent against disasters, purity (white).